ANALYSIS OF CITY LOGISTICS OF FOREIGN PLACES AND EXAMPLES WITH A SOLUTION - Fazekas, Miroslav; Sulgan, Marian (Doprava a spoje, 2012)
This article deals with City Logistics of large foreign cities. The article is about analysis of logistics solutions of foreign cities. The article describes specific examples of solutions City logistics that can be applied to Slovak cities. The goal of the article is to present other cities and their specific solutions of City logistic.